PERBEDAAN H-REFLEKS ANTARA NEUROPATHY ASSOCIATED with PREDIABETES DAN NEUROPATI DIABETIKA - , DANI PUJI LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Prediabetes is a stage of transition to diabetes mellitus (DM). Neuropathy occurred before Impaired Glucose Tolerance (IGT) developed diabetes so that the detection of neuropathy as early as possible is very useful for the management of patients with IGT f. H-reflex is recommended for detection of peripheral nerve damage. The aim of this study was to analyze the differences in the parameters of the H-reflex Neuropathy Associated with Prediabetes (NAP) and Diabetic Neuropathy (ND). This study used a cross-sectional study design. Subjects were 50 patients with NAP and 50 patients with ND. H-reflex Soleus examination carried out on the two groups to obtain the parameters of the H-reflex latency, M latency, H amplitude, the ratio Hmax/Mmax and excitatory threshold value of H reflex. Comparison of the H-reflex parameters showed statistically significant differences in all parameters of the H-reflex (p <0.05) between the NAP and ND. In conclusion, this study found differences in the H-reflex parameters between NAP and ND. Keywords: H-reflex soleus, Neuropathy Associated with Prediabetes, Diabetic Neuropathy